Optimalisasi Generator Dan Panel Kontrol Pada Alat Pembangkit Listrik Tenaga Sampah (Pltsa) Kapasitas 5 Kg - Muhlisin, Fajar Shohih; Marno , Marno; Anjani, Ratna Dewi (Jurnal Mesin Nusantara, 2023)
Part of the Waste Power Plant (PLTSa) is the control panel. In the previous research on its use, namely the type of generator with a power output of 500 W, with a voltage output of 11.9 V and the duration of charging the battery by the generator for 8 hours with the direct jumper method to the battery. The purpose of this study is to determine the process of obtaining current and voltage from the generator to the battery & to determine the battery charging speed. The research method for this PLTSa device is to consider the type & weight of the waste, vapor pressure, and the current voltage of the electric power generated using 2 blowers with 40 watts of power each. The results of calculating the battery charge for 8.8 hours. Based on the measurement results, with a mass of 5 kg of waste and a pressure of 6 bar, the burning time for firewood is 25 minutes, wooden blocks are 31 minutes and coconut shells are 35 minutes. At the maximum point, the current in the generator when it reaches 1243 rpm is 9 Ampere and the resulting voltage is 12.9 V, so the power obtained is 115.2 VA which can rotate two blowers. The conclusion of this study is that the charging speed of the battery in PLTSa equipment can be increased by changes to the specifications of the generator and SCC MPPT, eliminating Auto cut and Automatic Transfer Switch to streamline current loads.